Hemosiderotic fibrohistiocytic lipomatous lesion: clinical correlation with venous stasis - Kazakov, Dmitry V; Sima, Radek; Michal, Michal (Virchows Archiv, 2005)
Hemosiderotic fibrohistiocytic lipomatous lesion (HFLL) is a recently proposed lipomatous entity. HFLL was originally suggested to be a benign reactive lesion arising due to an antecedent trauma. We report two patients with HFLL who also suffered from chronic vein insufficiency due to varicose involving deep veins of the low limbs. Both patients were middle-aged women with solitary, poorly circumscribed subcutaneous lesions on the lower extremities. Histopathological examination revealed typical features of HFLL. We think that the consistent clinical features such as advanced age, female sex predilection, and specific location along with distinctive histopathological features allow the suggestion that impaired blood circulation, to wit, venous stasis is involved in the pathogenesis of HFLL. We hypothesize that the proliferation of spindled fibroblastic and myofibroblastic cells and capillaries, erythrocyte extravasation, and hemosiderin deposition with lipomatous tissue of HFLL may simply represent an exaggerated tissue response to venous stasis in which elevated venous and capillary pressures, oxygen saturation, and edema stimulate the proliferation of the above mentioned elements and lead to erythrocyte extravasation. A similar histopathological pattern is seen in acroangiodermatitis of Mali and vascular transformation of lymph node sinuses, and these conditions are also associated with impaired blood circulation.
Keywords: tuková tkáň; varixy; Soft Tissue Neoplasms; Venous Insufficiency; Humans; hemosiderin; lidé středního věku; Biomarkers, Tumor; histiocytóza; Female; žilní insuficience; výsledek terapie; lidé; Immunohistochemistry; imunohistochemie; nádory měkkých tkání; Varicose Veins; nádorové biomarkery; hemosideróza; ženské pohlaví; Hemosiderin; Middle Aged; Treatment Outcome; Histiocytosis; lipom; Adipose Tissue; Hemosiderosis; Lipoma